Thermographic Method Based Accelerated Fatigue Limit Calculation for Steel X5CrNi18-10 Subjected to Rotating Bending - Lipski Adam (Polish Maritime Research, 2015)
The article presents an accelerated method for fatigue limit calculation which makes use of constant temperature increase rate observed in the middle time interval of specimen fatigue loading. The examination was performed on specimens prepared from drawn rods made of corrosion resistant austenitic steel X5CrNi18-10 (1.4301) subjected to rotating bending. For comparison purposes, the fatigue limit was also calculated with the aid of the Staircase method, using 30 specimens and assuming the base number of cycles equal to 10·106. Three specimens were used for accelerated examination during which their temperature was measured with the aid of the thermographic camera CEDIP Silver 420M (FLIR SC 5200). The applied loads were gradually increased until specimen damage took place. Based on the analysis of temperature changes during specimen loading, the average rate of temperature increase at successive loading stages was assessed. The obtained results were then approximated using the 2-nd order curve and its minimal value was assumed as corresponding to the fatigue limit. The performed statistic test has revealed that the fatigue limit calculated in the above way does not differ substantially from that determined using the Staircase method.